Caracterização morfológica e análise da expressão gênica em arroz (Oryza sativa L.) sob estresse por ferro. - Bresolin, Adriana Pires Soares (2010)
Iron toxicity is one of the most important abiotic stresses limiting irrigated rice production worldwide. This study was performed with the goal of characterizing irrigated rice genotypes regarding Fe2+ stress tolerance under controlled conditions, using na hydroponic system. Furthermore, to analyse the expression profile of genes involved in iron homeostasis in plants, using quantitative PCR (qRT-PCR). The genotypes used were BRS-Agrisul, Epagri 108, BR-IRGA 409, BR-IRGA 410 and Nipponbare. An interference of the chelating agent (EDTA) was observed on the genotype characterization; when exposed to 0, 3, 6, 9 and 12 days of stress. The expression of genes OsFDRL1, OsNRAMP1 and OsNRAMP2 was measured at 0; 6; 12; 18 and 24h under Fe2+ stress. It was observed that Fe2+ in its free form without Na2EDTA, is acumulated in higher concentrations in the shoots of rice seedlings when compared to its chelated form (Fe-EDTA). Iron toxicity interfered negatively on the development of root length (RL) and shoot length (SL), being RL the variable that was most affected. Stress period increases led to iron accumulation in the shoots. The hydroponic system was efficient to allow discrimination between iron tolerant and sensitive genotypes. Iron sensitive genotypes observed in this study were BR-IRGA 409 and Nipponbare, which were those with higher iron accumulation in the shoots. Medium tolerant and tolerant genotypes also accumulated iron in the shoots. The increase in Fe2+ accumulation in the tissues under high iron stress was correlated with increased contents of Zn and Mn in the same tissues. Contrasting genotypes regarding iron tolerance showed differential expression of iron homeostasis genes OsFRDL1, OsNRAMP1 and OsNRAMP2.